2009
DOI: 10.1073/pnas.0904875106
|View full text |Cite
|
Sign up to set email alerts
|

A hyperfused mitochondrial state achieved at G 1 –S regulates cyclin E buildup and entry into S phase

Abstract: Mitochondria undergo fission-fusion events that render these organelles highly dynamic in cells. We report a relationship between mitochondrial form and cell cycle control at the G1-S boundary. Mitochondria convert from isolated, fragmented elements into a hyperfused, giant network at G1-S transition. The network is electrically continuous and has greater ATP output than mitochondria at any other cell cycle stage. Depolarizing mitochondria at early G1 to prevent these changes causes cell cycle progression into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
619
3
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 569 publications
(672 citation statements)
references
References 31 publications
31
619
3
6
Order By: Relevance
“…Progression from G1 to S phase during the cell cycle was shown to depend on hyperfusion of mitochondria. Also, mitochondrial fission was increased during mitosis [60][61][62]. These results further strengthen the general view that mitochondrial dynamics is strictly regulated at several levels (for a review see [63]).…”
Section: Mitochondrial Hyperfusion Helps To Ensure Mitochondrial Qualsupporting
confidence: 80%
“…Progression from G1 to S phase during the cell cycle was shown to depend on hyperfusion of mitochondria. Also, mitochondrial fission was increased during mitosis [60][61][62]. These results further strengthen the general view that mitochondrial dynamics is strictly regulated at several levels (for a review see [63]).…”
Section: Mitochondrial Hyperfusion Helps To Ensure Mitochondrial Qualsupporting
confidence: 80%
“…It is still unclear what is the mechanism contributing to the maintenance of the proliferation arrest. We speculate that a multitude of factors including the production of specific growth‐stimulating mitochondrial metabolites or interactions between mitochondria and cytoplasmic elements required for cell division may underlie the process (Mitra et al , 2009). The interplay between mitochondria and the mTOR signalling pathway may also be involved in this process, since we have shown that mitochondria clearance reduces mTOR activity and inhibition of mTOR activity inhibits proliferation contributing to quiescence.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, lower H 2 O 2 doses induced mitochondrial hyperfusion associated to decreased Fis1 expression levels and augmented Mfn1 and Mfn2 . Probably hyperfusion represents a cellular defensive response, because elongated mitochondria display higher efficiency in ATP production that may aid the recovery from the oxidative insult (Mitra et al, 2009;Tondera et al, 2009). In addition, the onset of the mitochondrial permeability transition, process frequently followed by mitochondrial network fragmentation and apoptosis, was subject to redox regulation by oxidation of some components of the mitochondrial permeability transition pore (MPTP), such as critical thiols in the adenine nucleotide translocase and nitration of tyrosines of the voltage-dependent anion channel (for a review see Daiber, 2010).…”
Section: The Feedback Loop Between Ros Production and Mitochondrial Dmentioning
confidence: 99%